Pengaruh Variasi Monoethanolamine dan Jumlah Pelapisan terhadap Band Gap Lapis Tipis CuSnO3 - Nengsi, Suharti; Sanjaya, Hary (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This study investigated a thin layer of CuSnO3 synthesized through sol-gel dip-coating method with variations in the addition of monoethanolamine. The results revealed that the addition of monoethanolamine by 1 ml reduced the band gap value to 2.2 eV, while the thin layer without the addition of monoethanolamine had a band gap value of 3.1 eV. In addition, the variation in the number of coatings also affects the band gap, where a maximum value of 2.1 eV is obtained with 2 times of coating. These results highlight the importance of monoethanolamine addition and coating amount in regulating the optical properties of CuSnO3 thin layers. The large amount of coating causes an increase in the band gap value and the addition of Monoethanolamine affects the CuSnO3 band gap value.